The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-84620-z
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model for the thermal enhancement of radiation response: thermodynamic approach

Abstract: Radiotherapy can effectively kill malignant cells, but the doses required to cure cancer patients may inflict severe collateral damage to adjacent healthy tissues. Recent technological advances in the clinical application has revitalized hyperthermia treatment (HT) as an option to improve radiotherapy (RT) outcomes. Understanding the synergistic effect of simultaneous thermoradiotherapy via mathematical modelling is essential for treatment planning. We here propose a theoretical model in which the thermal enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…This model provides a theoretical basis to understand hyperthermia-induced radiosensitization. Results showed that sensitization rates were exponentially dependent on temperature, which is in line with empirical observations [72]. Furthermore, it was shown that the model can reproduce clonogenic survival curves, as well as TER values observed in vitro and in vivo.…”
Section: Thermodynamic Modeling Based On the Lq-modelsupporting
confidence: 85%
See 1 more Smart Citation
“…This model provides a theoretical basis to understand hyperthermia-induced radiosensitization. Results showed that sensitization rates were exponentially dependent on temperature, which is in line with empirical observations [72]. Furthermore, it was shown that the model can reproduce clonogenic survival curves, as well as TER values observed in vitro and in vivo.…”
Section: Thermodynamic Modeling Based On the Lq-modelsupporting
confidence: 85%
“…Such evaluations could be very useful in the design of future prospective trials. De Mendoza et al proposed a thermodynamic model for simultaneous application of heat and radiation, in which the TER is related to the cell fraction that is radiosensitized by heat-induced sublethal damage [72]. Hyperthermia-induced damage will elevate cells from an alive state A to a more vulnerable sensitized state A'.…”
Section: Thermodynamic Modeling Based On the Lq-modelmentioning
confidence: 99%
“…Many mathematical models have been proposed to simulate the tissue temperature distribution in the tumor and surrounding healthy parts for treatment pre-planning with the aim of increasing the treatment efficacy and safety [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, substantial progress has been made in theoretical modeling to calculate and quantify the combined effect of radiation and hyperthermia [28][29][30][31]. Most notably, this has resulted in the temperature-dependent linear-quadratic (TDLQ) model [29] and its extended version, including direct temperature-induced cytotoxicity [30].…”
Section: Introductionmentioning
confidence: 99%